Current Trends in Neuromarketing Research: Bibliometric Review - Nafla Aqilah; Lissa Rosdiana Noer (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study provides a comprehensive bibliometric analysis of neuromarketing research published between 2020 and 2025, offering updated insights into the field's intellectual structure, key contributors, and evolving research themes. Utilizing data from the Scopus database and visualization tools such as VOSviewer, the research identifies the most cited authors, productive countries, influential journals, and dominant keywords in recent neuromarketing literature. Findings reveal three major clusters of co-citation networks representing theoretical foundations, applied neuroscience methods, and bibliometric analyses. The results highlight a growing interdisciplinary integration and methodological sophistication in neuromarketing, with increasing contributions from Asia alongside traditionally dominant Western countries. This study contributes to the consolidation of neuromarketing as a field by providing actionable insights for both academic researchers and marketing practitioners.